1995
DOI: 10.1088/0268-1242/10/8/023
|View full text |Cite
|
Sign up to set email alerts
|

4-11 mu m infrared emission and 300 K light emitting diodes from arsenic-rich InAs1-xSbxstrained layer superlattices

Abstract: Arsenic-rich InAs/lnAsr-,Sbx strained layer superlattices (SLSs) grown on GaAs substrates by molecular beam epitaxy (MBE) are studied for their potential application as infrared emitters. The long-wavelength emission (4-1 1 pm) is highly sensitive to superlattice design parameters and is accounted for by a large type4 band offset, greater than in previously studied antimony-rich InSb/lnAs,_,Sb, SLSs. High internal PL efficiencies (>lo%) and intense luminescence emission were observed at these long wavelengths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…As the potential barrier for the charge carriers increases, the overlap of electrons in the InAsSb and holes in the InAs decreases and thus the PL signal decreases. Tang et al 14 also observed similar very long wavelength emission from InAs/InAsSb superlattice light emitting diode structures grown on GaAs substrates. The long emission wavelength was attributed to type IIa band alignment ͑electrons confined to InAsSb͒.…”
mentioning
confidence: 63%
“…As the potential barrier for the charge carriers increases, the overlap of electrons in the InAsSb and holes in the InAs decreases and thus the PL signal decreases. Tang et al 14 also observed similar very long wavelength emission from InAs/InAsSb superlattice light emitting diode structures grown on GaAs substrates. The long emission wavelength was attributed to type IIa band alignment ͑electrons confined to InAsSb͒.…”
mentioning
confidence: 63%
“…This discrepancy is attributed to the neglect of the compositional disorder by the VCA method. Hence, a possible step beyond is to add to the VCA potential a non-periodic potential due to the compositional disorder as expressed in relation (2). By introducing the disorder effect potential to the VCA potential, the variation of E as a function of x is shown by the dotted curve in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This makes it an attractive material for a variety of mid-infrared optoelectronic devices, including lasers [2] and photo-detectors [3] and offers the possibility for replacing the HgCdTe materials most frequently used in the long-wavelength (8-12 m) and which are not easy to grow because of the difficulty in handling Hg [4]. Besides, InAs 1−x Sb x /InAs 1−y Sb y semiconductor alloys and hetero-junctions have been studied as potential infrared detectors and emitters [5].…”
Section: Introductionmentioning
confidence: 99%
“…The band offsets for the InΑs/ΙnΑs 1 -x Sbx superlattice system are the subject of some controversy with different groups variously putting forward type HA and type ΙIΒ alignments [1,2] on the basis of interband magnetoabsorption experiments performed at relatively low fields (< 10 T). In one case type I alignment coupled with strong narrowing of the band gap induced by Cu-Pt ordering in the alloy has also been proposed [3].…”
Section: Introductionmentioning
confidence: 99%